2020
DOI: 10.3389/fpls.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Mutagenesis of the TaCHLI Gene Suppressed Chlorophyll and Fatty Acid Biosynthesis in Common Wheat Seedlings

Abstract: Wheat (Triticum aestivum L.) is one of the most important crops in the world. Chlorophyll plays a vital role in plant development and crop improvement and further determines the crop productivity to a certain extent. The biosynthesis of chlorophyll remains a complex metabolic process, and fundamental biochemical discoveries have resulted from studies of plant mutants with altered leaf color. In this study, we identified a chlorophyll-deficiency mutant, referred to as chli, from the wheat cultivar Shaannong33 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…For example, Li et al ( 2020 ) found that a single nucleotide substitution in sedoheptulose 1,7-bisphosphatase ( SBPase ) severely affects plant growth and grain yield in rice. A single nucleotide mutation (G664A) in the TraesCS7A01G480700.1 ( chlI of Mg-chelatase) resulted in the mutant protein losing the ability to interact with the normal protein TaCHLI-7A (Wang et al, 2020 ). In A. thaliana , a single nucleotide substitution in DVR leading to one amino acid substitution in the protein did a partial loss of DVR function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Li et al ( 2020 ) found that a single nucleotide substitution in sedoheptulose 1,7-bisphosphatase ( SBPase ) severely affects plant growth and grain yield in rice. A single nucleotide mutation (G664A) in the TraesCS7A01G480700.1 ( chlI of Mg-chelatase) resulted in the mutant protein losing the ability to interact with the normal protein TaCHLI-7A (Wang et al, 2020 ). In A. thaliana , a single nucleotide substitution in DVR leading to one amino acid substitution in the protein did a partial loss of DVR function.…”
Section: Discussionmentioning
confidence: 99%
“…Shaannong 33 is a newly released high-quality, strong gluten wheat variety that has been approved in Shaanxi Province and introduced in Henan Province, China [ 88 , 89 ]. A summary and details of Shaannong 33 are shown in Table 4 , and the sister line of Shaannong 33, used as the control (CK), reported with low-quality traits, given in Table 1 , represents three-year field trails.…”
Section: Methodsmentioning
confidence: 99%
“…Leaf color variation is an important mutation for improving photosynthesis and increasing yield potential. In fact, several stably inheritable leaf color variations have been discovered in wheat (Dlm, lm3, Ygm and chli), providing abundant genetic resources for breeding wheat with high photosynthetic efficiency and ideal yield potential [4][5][6][7]. Most leaf color mutants can be primarily divided into two types: homogeneous (just one leaf color: albina, xantha mutations) and heterogeneous (two or more leaf colors: alboviridis, viridis, or tigrina mutations).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, displaying distinct leaf colors at different growth phases would result in a more diversified and perceptible leaf landscape. Wang et al reported a pale-green leaf mutant (chli) presenting greenish leaves from the one-leaf stage and re-green at the heading stage [7]. The results revealed no change in kernel quantity or seed setting rate with the wide type, but a notable reduction in tiller number.…”
Section: Introductionmentioning
confidence: 99%